2020
DOI: 10.1002/1348-9585.12136
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of exposure to extremely low frequency electromagnetic fields on job burnout syndrome and the severity of depression; the role of oxidative stress

Abstract: Objectives This study was designed to investigate the possible effect of exposure to extremely low frequency electromagnetic fields (ELF‐EMFs) on occupational burnout syndrome and the severity of depression experienced among thermal power plant workers and the role of oxidative stress. Methods In this cross‐sectional study, 115 power plant workers and 124 administrative personnel of a hospital were enrolled as exposed and unexposed groups, respectively, based on inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…According to some studies, ELF-EMF is the same as physiological stress and can cause oxidative stress in the brains of rats [20], chick embryonic cells and humans erythrocytes [21], and kestrel lymphocytes [22]. Numerous studies has been performed on behavior of animal which indicates that ELF-EMF are safe in some cases [23,24] but they are abundant studies declaring of hazardous effect of them in promoting anxiety and depression behaviors in animals [25][26][27] and human [28,29]. On the other hand, another research has demonstrated some anti-anxiety effects of low frequency electromagnetic fields in mice [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, ELF-EMF is the same as physiological stress and can cause oxidative stress in the brains of rats [20], chick embryonic cells and humans erythrocytes [21], and kestrel lymphocytes [22]. Numerous studies has been performed on behavior of animal which indicates that ELF-EMF are safe in some cases [23,24] but they are abundant studies declaring of hazardous effect of them in promoting anxiety and depression behaviors in animals [25][26][27] and human [28,29]. On the other hand, another research has demonstrated some anti-anxiety effects of low frequency electromagnetic fields in mice [30].…”
Section: Introductionmentioning
confidence: 99%
“…MDA, SOD, and CAT levels in the group exposed to low-frequency EMF were significantly lower than those in the nonexposed group. The prevalence of burnout syndrome and severity of depression were also higher in the former group 13 . These results suggest that oxidative stress induced by RF-EMF can lead to DNA damage in neurons during prolonged exposure to animals.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, ELF-EMF-induced oxidative stress contributes to mitochondrial dysfunction. Since mitochondria plays a role in ATP generation, their dysfunction could cause energy deficit in the body and burnout syndrome 2 .…”
Section: Discussionmentioning
confidence: 99%
“…International Agency for Research on Cancer (IARC) classified ELF-EMF among probable human carcinogens (group 2B), but some studies observed a significant association between exposure to these fields and the prevalence of leukemia, breast, and brain cancer 4 . Headache, burnout, depression, anxiety, and fatigue caused by the effect of the fields on one's sleep were also reported among subjects exposed to the ELF-EMF 2 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation